REGISTER LAPORAN PANDANGAN MATA KOMENTATOR SEPAKBOLA (Sebuah Kajian Sosiolinguistik) - Wahyu Utomo, Dhafid (Jurnal Sasindo UNPAM, 2014)
Football game commentator is one of the professions in the field of football game whose duty is to describe the process of the football match as well as to give  information around the game to the viewers. This research is aimed at studying linguistics or register variations which are more focused on the linguistic features and specific lexical meanings that appear. Data collecting is executed through listening method by employing recording as the primary technique and non- participated listening technique as the secondary technique. This research is able to identify four linguistic featuresand specific lexicons in term of the eye sight report register in commentator football match. The conclusion that can be derived is that the existence of commentator in a football game intends to enhance the attractive force of the game itself.         Key words: register, lingistic features, jargon.